The Influence of Investor Sentiment, Dividend Yield, and Trade Volume on the Stock Price Volatility of Banking Sector Companies at the IDX - Alfareza, Muhammad Rifat Noer; Susilo (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to analyze the effect of investor sentiment, dividend yield, and trading volume on the stock price volatility of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using panel data regression on 10 banking companies, resulting in a total of 40 observations. The model selection results indicate that the Random Effect Model (REM) estimated using the Generalized Least Squares (GLS) approach is the most appropriate estimation method. The findings reveal that investor sentiment has a positive and significant effect on stock price volatility, indicating that psychological factors play a more dominant role in shaping stock price dynamics within the banking sector. In contrast, dividend yield and trading volume do not have a significant effect on stock price volatility. These results suggest that stock price volatility in the banking sector during the observed period is more strongly driven by investors perceptions and expectations. This study is expected to provide valuable insights for investors in understanding the dynamics of the Indonesian stock market.